Existing equations to estimate lean body mass are not accurate in the critically ill: Results of a multicenter observational study. Issue 6 (December 2017) - Moisey, Lesley L.; Mourtzakis, Marina; Kozar, Rosemary A.; Compher, Charlene; Heyland, Daren K.
Summary: Background & aims: Lean body mass (LBM), quantified using computed tomography (CT), is a significant predictor of clinical outcomes in the critically ill. While CT analysis is precise and accurate in measuring body composition, it may not be practical or readily accessible to all patients in the intensive care unit (ICU). Here, we assessed the agreement between LBM measured by CT and four previously developed equations that predict LBM using variables (i.e. age, sex, weight, height) commonly recorded in the ICU. Methods: LBM was calculated in 327 critically ill adults using CT scans, taken at ICU admission, and 4 predictive equations (E1–4) that were derived from non-critically adults since there are no ICU-specific equations. Agreement was assessed using paired t -tests, Pearson's correlation coefficients and Bland–Altman plots. Results: Median LBM calculated by CT was 45 kg (IQR 37–53 kg) and was significantly different (p < 0.001) from E1 (52.5 kg; IQR: 42–61 kg), E2 (55 kg; IQR 45–64 kg), E3 (55 kg; IQR 44–64 kg), and E4 (54 kg; IQR 49–61 kg). Pearson correlation coefficients suggested moderate correlation (r = 0.739, 0.756, 0.732, and 0.680, p < 0.001, respectively). Each of the equations overestimated LBM (error ranged from 7.5 to 9.9 kg), compared with LBM calculated by CT, suggesting insufficient agreement. Conclusions: Our data indicates a large bias is present between the calculation of LBM by CT imaging and the predictive equations that have been compared here. This underscores the need for future research toward the development of ICU-specific equations that reliably estimate LBM in a practical and cost-effective manner.